2017
DOI: 10.12928/telkomnika.v15i1.3804
|View full text |Cite
|
Sign up to set email alerts
|

Privacy and Personal Data Protection in Electronic Voting: Factors and Measures

Abstract: In general, electronic voting as the technology advancement offers the opportunities to reduce the time and budget of implementation which present the greater advantages than traditional approach. It seeks establish the privacy framework in the context of electronic voting that aligns with the mutual comprehension of relevant factors and measures. The result found that privacy concern and perceived benefit have influenced personal data protection significantly. The success and failure of electronic voting impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…In short, the assumption of arbitrary power abuse by some parties encouraged them to express their opinion in the Twitter. It is aligned with other research [17] found that only a minority understood the UU ITE really well and applied it in their daily operations either in the individual task or at company operation consistently and strictly while the majority of Indonesians knew nothing about it at all. There were so many companies in Indonesia, which had just started operations and were still ignorant of the rules and regulations governing this sector a nd at the same time did not feel obliged to consult legal experts.…”
Section: Precedencesupporting
confidence: 87%
“…In short, the assumption of arbitrary power abuse by some parties encouraged them to express their opinion in the Twitter. It is aligned with other research [17] found that only a minority understood the UU ITE really well and applied it in their daily operations either in the individual task or at company operation consistently and strictly while the majority of Indonesians knew nothing about it at all. There were so many companies in Indonesia, which had just started operations and were still ignorant of the rules and regulations governing this sector a nd at the same time did not feel obliged to consult legal experts.…”
Section: Precedencesupporting
confidence: 87%
“…In networking devices and cyber worlds, people are usually expected to recognize a latest collection of the restriction in order to realize the importance of privacy right within the realms. The perspective of communication process has indicated particularly effective as a beginning point for academic discussion and observational studies of privacy compare to the practical use of IT, at least to social media and emerging issues influenced by its rapid advancement [69].…”
Section: A Privacy Concern and Rightsmentioning
confidence: 99%
“…In addition, the universal verifiability requirement can be viewed as means to assure correctness, increase personal data protection and avoid electoral fraud although, to some extent, it has conflict with the process of ballot validation [28]. In the context of election, based on the user perspective through survey, the legal standards was is not sufficient to effectively regulate the development and the voting machines adoption, particularly, in respect to approved security mechanism, performance indicator, tabulation program, assessment technique and certification process [34].…”
Section: The Role Of Technology As Solutionmentioning
confidence: 99%